A Man with Uterine Leiomyoma as Part of Persistent Müllerian Duct Syndrome – a Case Report and Review of the Literature - Ivan Novak; Igor Grubišić; Ivan Pezelj; Tihana Regović Džombeta; Ivan Svaguša; Goran Štimac; Monika Ulamec; Božo Krušlin (Acta Clinica Croatica)
We present a clinical case of a 59-year-old man, father of two children, who complained of irritative voiding of the bladder. An unknown retrovesical structure was detected by ultrasound and computed tomography, and was surgically removed later. Histopathologic analysis reported uterine tissue with a leiomyoma, thus the diagnosis of persistent müllerian duct syndrome (PMDS) was established. It is a rare disorder characterized by the appearance of müllerian derivatives (fallopian tubes, uterus, and upper two-thirds of vagina) in males with normally developed external and internal genitalia. Patients usually present with cryptorchidism and inguinal hernia. Irritative voiding has not yet been described as the main symptom of PMDS. The major complications of the disorder are infertility, testicular tumorigenesis, and malignant transformation of müllerian structures. To the best of our knowledge, in addition to our case, only one case of PMDS with uterine leiomyoma has been described in the literature so far.